Deciphering the molecular signatures of tropical Areca catechu L. under cold stress: an integrated physiological and transcriptomic analysis - Li, Han; Zhang, Linbi; Wen, Xinyu; Ji, Changlei; Chen, Hui; Tian, Meng; Yang, Fusun; He, Jun (Frontiers in Plant Science, 2025)
IntroductionAreca catechu is a widely cultivated palm species with significant economic and medicinal value. However, A. catechu is a tropical plant that is particularly susceptible to low temperatures.MethodsThis study integrates physiological profiling with transcriptomic sequencing to systematically investigate the cold-response mechanisms of A. catechu.ResultsMultivariate variance analysis revealed that peroxidase (POD) activity and chlorophyll content are significant biomarkers strongly correlated with cold tolerance. A comprehensive investigation into the temporal expression of genes in response to 24 hours of cold stress was conducted, using RNA-seq analysis. This analysis yielded a substantial number of differentially expressed genes (DEGs), amounting to 20,870, which were found to be subject to temporal regulation. KEGG pathway enrichment analysis revealed substantial activation in three metabolic pathways: phytohormone signaling, alkaloid biosynthesis (tropane/piperidine/pyridine), and flavonoid biosynthesis. The application of Weighted Gene Co-expression Network Analysis (WGCNA), in conjunction with a dynamic tree-cutting algorithm, resulted in the identification of 25 co-expression modules. Eigenvector centrality analysis identified six hub genes responsive to cold stress: ZMYND15, ABHD17B, ATL8, WNK5, XTH3 and TPS. The findings of this study delineate three key aspects: (1) temporal dynamics of cold-responsive physiological processes, (2) pathway-level characterization of DEG enrichment patterns, and (3) genetic determinants underlying cold stress adaptation.DiscussionThese findings clarify the time series and core physiological indicators of A. catechu during various physiological processes, identify pivotal genes associated with cold stress, and provide a gene-to-phenotype framework for optimizing cold-resilient cultivation protocols and molecular marker-assisted breeding strategies.